2022
DOI: 10.1155/2022/5188311
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture in the Treatment of Poststroke Insomnia: A Systematic Review and Meta-Analysis of Twenty-Six Randomized Controlled Trials

Abstract: Objective. To evaluate the efficacy and safety of acupuncture in the treatment of poststroke insomnia. Methods. PubMed, the Cochrane Library, Embase, Web of Science, China Biology Medicine (CBM), CNKI, VIP, and Wanfang databases were searched by computer from their inception to April 29, 2021, for collecting all randomized controlled trials of acupuncture in the treatment of poststroke insomnia. After two reviewers independently screened the literature, extracted the data, and evaluated the risk of bias in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition to acupuncture and acupressure, ASRTs have now evolved into numerous treatment techniques driven by clinical need, with acupoint selection varying from practitioner to practitioner. While several clinical common ASRTs for insomnia have been evaluated in previous systematic reviews, [45][46][47][48][49][50][51][52][53] in the face of such a wide range of ASRTs, there is no conclusion on how ASRT clinicians should manage insomnia in clinical practice. To develop guidelines and further drive future clinical practice and research, a more thorough and comprehensive evaluation of all the existing literature is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acupuncture and acupressure, ASRTs have now evolved into numerous treatment techniques driven by clinical need, with acupoint selection varying from practitioner to practitioner. While several clinical common ASRTs for insomnia have been evaluated in previous systematic reviews, [45][46][47][48][49][50][51][52][53] in the face of such a wide range of ASRTs, there is no conclusion on how ASRT clinicians should manage insomnia in clinical practice. To develop guidelines and further drive future clinical practice and research, a more thorough and comprehensive evaluation of all the existing literature is required.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Numerous systematic reviews have also reported that the efficacies of these common clinical ASRTs for primary insomnia and comorbid insomnia were higher than that of routine care, placebo acupuncture, or waiting list controls. [45][46][47][48][49][50][51][52][53] However, the generalizability of these findings was constrained by the fact that the quality of the available literature is generally poor and these meta-analyses concentrated on a particular form of insomnia and/or a single therapy approach.…”
Section: Introductionmentioning
confidence: 99%
“…70 Nonetheless, active acupuncture was shown to be minimally superior to placebo acupuncture. 70 A meta-analysis of acupuncture for preoperative anxiety 71,72 and poststroke insomnia 73 reported a similar low study quality. A study of 72 patients with primary insomnia revealed that acupuncture was more effective than sham acupuncture for most sleep measures.…”
Section: Acupuncturementioning
confidence: 97%
“…Multiple randomized controlled trials have shown that acupuncture serves as a useful tool for patients with post-stroke sleep disorders [225][226][227]. Recently, acupuncture therapy, as a traditional Chinese medicine therapy, has been widely used in the treatment of post-stroke sleep disorders for its convenient operation and low adverse effect characteristics [228][229][230][231].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%